PERENCANAAN ULANG STRUKTUR ATAS JEMBATAN MENGGUNAKAN BALOK-T BETON BERTULANG JL. BROMO KECAMATAN BARENG JOMBANG - Wafi, Wafi sofwan nadi (Teknosia, 2024)
Bridges are one of the important infrastructures in the transportation system that play a role in connecting two locations separated by rivers, valleys, or other roads. The Jl. Bromo Bridge is planned to span 10 meters. Initially, this bridge used an arched type structure that was built during the Netherlands colonial period so that there was a need for structural rejuvenation due to the increasing volume of vehicles. The researcher replanned using a conventional concrete girder of T type by calculating the loading aspect referring to SNI 1275-2016, planning the repetition and repetition dimensions on the T-girder, and deflection control on the bridge. The results of the calculation on the replanning of the bridge upper structure were obtained as a result of the sidewalk weight (PMS) of 17.13 kN (MMS) 12.87 kNm, the nominal moment of the plan on the backrest wall was 0.0076, the reinforcement area was 152,233 mm2, the reinforcement D was 16 - 130 mm. The sliding span used is D 13 – 250 mm. The results of the calculation of the ultimate moment of loading (MU) that occurred on a beam of 1,482 kNm and the ultimate shear force (VU) of 598.44 kN with beam reinforcement were used 5 D32 with stiff reinforcement 22 – 100 mm. combination of deflection 0.017 < 10/240 = 0.042, with the use of diaphragm 2 D19 reinforcement, with a stiff reinforcement of 16 -120 mm.